The Transformation of Research Supporting Libraries: Case Study Knowledge-Sharing as Organizational Culture at the National Research and Innovation Agency Library - Nur Fauziyah, Mayang Rumaisha; Yustikasari, Yustikasari (Department Library of Governance Institut of Home Affairs, 2024)
Background: The rapid advancement of technology and information has necessitated libraries to transform respective services in order to remain relevant and effective. To achieve relevance and effectiveness, libraries must cultivate an organizational culture that supports necessary transformations, particularly in the field of library services. In particular, libraries that significantly support research have been found to continually innovate respect offerings with the sole purpose of providing information capable of facilitating the research process. Purpose: This research aimed to examine the support provided by the National Research and Innovation Agency (BRIN) for the successful documentation of publications, with a specific focus on the evolving services offered by the library. Method: The research method used is qualitative research with a case study approach. Result:The BRIN Library offers a variety of services, including research consultation, information retrieval, bibliometric analysis, data visualization, literature review support, and plagiarism detection. In order to achieve the stated objective, a qualitative method was adopted with a case study approach to explore the phenomenon of knowledge-sharing in the context of library transformation as part of its organizational culture. Conclusion: The obtained results showed that knowledge-sharing activities at BRIN Library played a significant role in enhancing the expertise of librarians and improving the quality of research services. These services were observed to be facilitated through formal and informal programs, egalitarian leadership practices, as well as internal and external motivational strategies. It was also found that BRIN librarians actively contributed to research innovation in Indonesia by enabling access to critical information, promoting information literacy, and fostering collaboration among academics. Based on the findings, knowledge-sharing activities within libraries supporting research were inferred to lead to the cultivation of an organizational culture that promotes interdisciplinary and inter-institutional collaboration.